Study Of Hearing Loss In Neonates Born To Diabetic Mothers - Hugar, Rajeshkumar; D. Havle, Abhay; Colvin, Sweta; Shedge, Swapna Ajay; M P, Aditya; S J, Vigneshwar (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus during pregnancy represents a significant health concern that can lead to various complications affecting both maternal and fetal well-being. The association between maternal diabetes and adverse neonatal outcomes has been extensively studied, with increasing evidence suggesting its impact on auditory function in newborns. Objective: To determine the incidence of hearing loss in neonates born to mothers with pre-gestational and gestational diabetes mellitus and to correlate the types and degree of neonatal hearing loss with maternal HbA1C levels. Methods: This prospective observational study was conducted at Krishna Vishwa Vidyapeeth, Karad, involving 67 neonates born to diabetic mothers. Maternal diabetes was evaluated through glycated haemoglobin (HbA1c) measurement. Neonatal hearing assessment employed Otoacoustic Emission (OAE) testing during the neonatal period (0-28 days), followed by Auditory Brainstem Response (ABR) testing at 3 and 6 months of age. Results: Among 67 neonates, 2 (3%) developed confirmed hearing loss. All cases were bilateral sensorineural hearing loss of moderately severe degree. Both cases occurred in neonates born to mothers with poor glycemic control (HbA1c >7.0%). Initial OAE screening showed abnormal results in 34.3% of neonates, which reduced to 3% on definitive ABR testing. All neonates with confirmed hearing loss required NICU admission and experienced birth complications. Conclusion: The study confirms maternal diabetes as a significant risk factor for neonatal hearing impairment, with poor glycemic control being the critical determinant. Universal audiological screening of neonates born to diabetic mothers is recommended, with particular vigilance for those with poor maternal glycemic control and birth complications.